Juvenile localized scleroderma with port wine stain: Coincidental or possible common pathogenetic association - Seval Dogruk Kacar (Indian Journal of Dermatology, 2015)
Port wine stain and juvenile localized scleroderma are two different dermatoses usually encountered in pediatric age group. Up to now, there are reports of morphea patients initially diagnosed and treated as port wine stain. Coexistence of both diseases is not found yet. We herein present a case of juvenile localized scleroderma on the left side of trunk, with congenital port wine stain located on the ipsilateral face at V1-V2 distribution.